Preparation method of metallic glass-epoxy resin composite film and friction power generation element

By doping metal glass powder into the epoxy resin film, the metal glass-epoxy resin composite film is formed, which solves the problems of charge leakage and loss in high humidity environments, improves the charge accumulation and retention ability of friction power generation components, and improves the power generation efficiency.

CN119708569APending Publication Date: 2025-03-28CHONGQING NORMAL UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411932666.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In high humidity environments, the surface of the epoxy resin film is prone to adsorbing moisture, resulting in leakage and loss of charge, affecting the generation and maintenance of charge, and reducing power generation efficiency.

Method used

The preparation method of metal glass-epoxy resin composite film is adopted to form a composite film by doping preset metal glass powder into the epoxy resin and the curing agent liquid to improve the accumulation and maintenance of charge.

Benefits of technology

Through doping of metal glass powder, the amount of flowing charges is increased, the charge transfer characteristics are improved, energy release is reduced, and the accumulation and retention of charges is enhanced, thereby improving the performance and efficiency of friction power generation components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708569A_ABST
    Figure CN119708569A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a metallic glass-epoxy resin composite film and a friction power generation element, and relates to the technical field of composite materials. Epoxy resin and curing agent liquid are used as matrixes; determining preset metal glass powder corresponding to the epoxy resin liquid according to the mass ratio; and doping preset metal glass powder into the epoxy resin and the curing agent liquid in the matrix to form the metal glass-epoxy resin composite film. According to the invention, through doping of the metal glass powder, the number of flowing charges is increased, so that the performance of the composite film power generation element is improved. The charge transfer characteristic is changed in the process, so that more shallow traps are formed in an interface region between the metal glass powder and the epoxy resin matrix, and less energy is released in the charge carrier process. Meanwhile, the preset metal glass powder with the determined mass ratio is introduced to improve accumulation and retention of charges, and the performance and efficiency of the power generation element are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a preparation method of a metallic glass-epoxy resin composite film and a friction power generation element. Background Art

[0002] Epoxy resin itself is a good insulating material, which is essential for triboelectric generation.

[0003] The charge generated by the epoxy resin film during the friction power generation process is easily affected by environmental factors, such as humidity, temperature, etc. In a high humidity environment, the surface of the epoxy resin film is easy to absorb moisture, resulting in the leakage and loss of charge, affecting the generation and retention of charge, and thus reducing the power generation efficiency.

[0004] Therefore, how to improve the generation and retention of charge during the friction process and reduce charge leakage and loss is an urgent problem that technicians in this field need to solve. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a metallic glass-epoxy resin composite film and a friction power generation element to solve the problem that in a high humidity environment, the surface of the epoxy resin film is easily adsorbed with moisture, resulting in leakage and loss of charge, affecting the generation and retention of charge, and thus reducing the power generation efficiency.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a metallic glass-epoxy resin composite film, comprising:

[0007] It is based on epoxy resin and curing agent liquid;

[0008] Determine the preset metallic glass powder corresponding to the epoxy resin liquid according to the mass ratio;

[0009] Preset metallic glass powder is doped into the epoxy resin and curing agent liquid in the matrix to form the metallic glass-epoxy resin composite film.

[0010] On the one hand, the predetermined metallic glass powder is doped into the epoxy resin and the curing agent liquid in the matrix, comprising:

[0011] Based on room temperature, the preset metallic glass powder is rotated and mixed into the epoxy resin and the curing agent liquid in the matrix at a preset speed.

[0012] On the other hand, the process of determining the mass ratio comprises:

[0013] Obtaining each preset mass ratio and the mass of the epoxy resin liquid;

[0014] Determining each initial preset metallic glass powder corresponding to each preset mass ratio according to each preset mass ratio and the mass of the epoxy resin liquid;

[0015] According to the epoxy resin liquid corresponding to each of the preset mass ratios and the corresponding initially preset metallic glass powder, a corresponding charge quantity and a corresponding current average value are prepared;

[0016] A final mass ratio is determined based on the charge quantity and / or the current average value.

[0017] On the other hand, determining the final mass ratio according to the current average value comprises:

[0018] Screening out the maximum current average value among the current average values ​​corresponding to the preset mass ratios;

[0019] The preset mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

[0020] On the other hand, determining a final mass ratio according to the charge quantity and the current average value comprises:

[0021] Get the preset charge quantity;

[0022] Selecting a mass ratio greater than the preset charge quantity from each charge quantity as the initial mass ratio;

[0023] Screening out the largest current average value from the current average values ​​corresponding to the initial mass ratios;

[0024] The initial mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

[0025] On the other hand, the mass ratio of the preset metallic glass powder to the epoxy resin liquid is less than 10%.

[0026] On the other hand, the metallic glass powder is FeNiCoZr metallic glass powder, and the oxygen content of the FeNiCoZr metallic glass powder is less than 1%.

[0027] On the other hand, the powder particle size of the metallic glass powder is 20-50 μm.

[0028] In order to solve the above technical problems, the present invention also provides a friction power generation element, including a copper electrode layer, a charge transfer layer and a flexible friction layer; the size of the friction power generation element is 46×90mm 2 , thickness 1µm; wherein the film inside the charge transport layer is a metallic glass-epoxy resin composite film prepared according to the steps of the above-mentioned method for preparing a metallic glass-epoxy resin composite film;

[0029] The flexible friction layer is located on the outer layer of the friction power generation element and is used for contacting with the outside world to generate friction charges;

[0030] The charge transfer layer is located between the flexible friction layer and the copper electrode layer, and is used to transfer the friction charges to the copper electrode layer;

[0031] The copper electrode layer is located in the inner layer of the friction power generation element and is used to collect the friction charges.

[0032] In order to solve the above technical problems, the present invention also provides a wearable electronic device, comprising the above-mentioned friction power generation element.

[0033] The present invention provides a preparation method based on a metallic glass-epoxy resin composite film, which uses epoxy resin and curing agent liquid as a matrix; determines a preset metallic glass powder corresponding to the epoxy resin liquid according to a mass ratio; and dopes the preset metallic glass powder into the epoxy resin and curing agent liquid in the matrix to form a metallic glass-epoxy resin composite film. The present invention improves the performance of the composite film power generation element by doping the metallic glass powder to increase the number of mobile charges. This process changes the charge transfer characteristics, so that more shallow traps are formed in the interface area between the metallic glass powder and the epoxy resin matrix, and less energy is released in the charge carrier process. At the same time, the preset metallic glass powder determined by the mass ratio is introduced to improve the accumulation and retention of charges, thereby improving the performance and efficiency of the power generation element.

[0034] In addition, the present invention also provides a friction power generation element and a wearable electronic device, which have the same beneficial effects as the above-mentioned preparation method based on the metallic glass-epoxy resin composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 A flow chart of a method for preparing a metallic glass-epoxy resin composite film provided in an embodiment of the present invention;

[0037] Figure 2 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 0.5% provided in an embodiment of the invention;

[0038] Figure 3 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 2.5% provided in an embodiment of the invention;

[0039] Figure 4 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 5% provided in an embodiment of the invention;

[0040] Figure 5 A schematic diagram of a metallic glass powder and epoxy resin having a mass ratio of 7.5% provided in an embodiment of the invention;

[0041] Figure 6 A schematic diagram of a metallic glass powder to epoxy resin mass ratio equal to 10% provided in an embodiment of the invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The core of the present invention is to provide a method for preparing a metallic glass-epoxy resin composite film and a friction power generation element to solve the problem that in a high humidity environment, the surface of the epoxy resin film is easily adsorbed with moisture, resulting in leakage and loss of charge, affecting the generation and retention of charge, and thus reducing the power generation efficiency.

[0044] In order to enable those skilled in the art to better understand the solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0045] Figure 1 A flow chart of a method for preparing a metallic glass-epoxy resin composite film provided in an embodiment of the present invention is shown in FIG. Figure 1 As shown, the method includes:

[0046] S11: based on epoxy resin and curing agent liquid;

[0047] S12: determining a preset metallic glass powder corresponding to the epoxy resin liquid according to the mass ratio;

[0048] S13: doping a preset metallic glass powder into the epoxy resin and the curing agent liquid in the matrix to form a metallic glass-epoxy resin composite film.

[0049] Specifically, the composite film is based on epoxy resin and curing agent liquid, metallic glass powder is doped into the matrix, the metallic glass powder is doped into the epoxy resin and curing agent liquid by high-speed rotation at room temperature, and then cooled at room temperature to form a metallic glass-epoxy composite film. The composite film is selected according to the mass ratio of the metallic glass powder to the epoxy resin liquid.

[0050] The mass ratio here can be determined by comparing a plurality of different preset mass ratios to determine the final mass ratio, or it can be directly obtained based on experimental data, which is not limited here.

[0051] In some embodiments, the process of determining the mass ratio includes:

[0052] Obtain each preset mass ratio and the mass of the epoxy resin liquid;

[0053] Determine each initial preset metallic glass powder corresponding to each preset mass ratio according to each preset mass ratio and the mass of the epoxy resin liquid;

[0054] According to the epoxy resin liquid corresponding to each preset mass ratio and the corresponding initially preset metallic glass powder, a corresponding charge quantity and a corresponding current average value are prepared;

[0055] The final mass ratio is determined based on the charge number and / or current average.

[0056] Specifically, by setting different preset mass ratios, the initial preset metallic glass powders corresponding to the preset mass ratios are determined according to the different preset mass ratios and the mass of the epoxy resin liquid. The corresponding charge quantity and the corresponding current average value are experimentally prepared, and the final mass ratio is determined based on two parameters or one parameter, that is, using the relationship of and / or. That is, the final mass ratio can be determined according to the charge quantity and the current average value, or the final mass ratio can be determined according to the charge quantity, or the final mass ratio can be determined by the current average value. The specific determination process is not limited and can be set according to actual conditions.

[0057] This embodiment provides a method for determining the final mass ratio based on different preset mass ratios to improve the accuracy of mass ratio screening and enhance the performance of the prepared composite film.

[0058] In some embodiments, determining the final mass ratio according to the current average value includes:

[0059] Screening out the maximum current average value among the current average values ​​corresponding to each preset mass ratio;

[0060] The preset mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

[0061] The maximum current average value is selected from the current average values ​​corresponding to the preset mass ratios, and the preset mass ratio corresponding to the maximum current average value is used as the final mass ratio. It should be noted that the final mass ratio in this embodiment is one, and multiple mass ratios can also be used for preparation, etc., which is not limited here.

[0062] In this embodiment, the final mass ratio is screened by the current average value, which simplifies the screening process and improves the preparation efficiency.

[0063] In some other embodiments, determining the final mass ratio according to the charge quantity and the current average value includes:

[0064] Get the preset charge quantity;

[0065] Selecting a mass ratio greater than a preset charge quantity from each charge quantity as an initial mass ratio;

[0066] Screening out the largest current average value from the current average values ​​corresponding to the initial mass ratios;

[0067] The initial mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

[0068] Specifically, here we first select the mass ratio corresponding to the charge quantity exceeding the preset charge quantity as the initial mass ratio, select the largest current average value from the current average values ​​corresponding to each initial mass ratio, and use the corresponding initial mass ratio as the final mass ratio.

[0069] In the screening process of the mass ratio provided in this embodiment, the two parameters of charge quantity and current average value are used to determine the mass ratio, thereby improving the accuracy of the screening.

[0070] Figure 2 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 0.5% provided in an embodiment of the invention, Figure 3 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 2.5% provided in an embodiment of the invention, Figure 4 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 5% provided in an embodiment of the invention, Figure 5 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 7.5% provided in an embodiment of the invention, Figure 6 A schematic diagram of a metallic glass powder and epoxy resin mass ratio equal to 10% provided in an embodiment of the invention. Figures 2 to 6 As shown, the average current values ​​are 154nA, 167nA, 182nA, 96nA and 90nA respectively. It can be seen from the figure that the largest corresponding average current value is 182nA, and the preferred mass ratio is 5%.

[0071] In some embodiments, the mass ratio of the metallic glass powder to the epoxy resin liquid is preset to be less than 10%.

[0072] Combination Figures 2 to 6As the mass ratio increases, the average current value first shows an upward trend, then reaches a peak value and then decreases. There is no trend of continuing to rise. Therefore, considering that if the mass ratio exceeds 10%, the average current value decreases, the mass ratio is limited to a range here, that is, less than 10%.

[0073] The preset mass ratio of the metallic glass powder to the epoxy resin liquid provided in this embodiment is less than 10%, thereby increasing the amount of charge accumulation under the average current value.

[0074] In some embodiments, the predetermined metallic glass powder is doped into the epoxy resin and the curing agent liquid in the matrix, comprising:

[0075] Based on room temperature, the preset metallic glass powder is rotated and doped into the epoxy resin and the curing agent liquid in the matrix at a preset speed.

[0076] Specifically, a high-speed rotation experiment of doping a preset metallic glass powder into an epoxy resin and a curing agent liquid at a preset speed increases the effect of reducing charge leakage after increasing the number of mobile charges. First, the metallic glass powder is weighed according to a predetermined ratio, and the epoxy resin and the curing agent liquid are prepared. The metallic glass powder is slowly added to the epoxy resin and the curing agent liquid, and the high-speed rotation mixing device is turned on at the same time to evenly disperse the powder in the epoxy resin. The temperature of the constant temperature water bath is controlled to ensure that the experiment is carried out at room temperature to avoid the influence of temperature on the experimental results. Continue to rotate at high speed for a certain period of time to ensure that the metallic glass powder is fully mixed with the epoxy resin and the curing agent liquid. High-speed rotation can make the metallic glass powder more evenly dispersed in the epoxy resin and the curing agent liquid, increase the interface contact area, and thus increase the number of mobile charges. The doping of metallic glass powder may change the internal microstructure of the epoxy resin, improve its thermal stability, and thus reduce charge leakage.

[0077] The process of doping the metallic glass powder provided in this embodiment into the epoxy resin and the curing agent liquid by high-speed rotation at room temperature makes the metallic glass powder dispersed more evenly in the epoxy resin and the curing agent liquid, increases the interface contact area, and thus increases the number of mobile charges. The doping of the metallic glass powder may change the internal microstructure of the epoxy resin, improve its thermal stability, and thus reduce charge leakage.

[0078] It should be noted that the specific doping method to increase the number of charges can be friction, electrostatic induction, ionization, high-voltage electrostatic generator, etc. The friction method can charge the metallic glass powder by rubbing it with another material. This method is simple and easy. The electrostatic induction method uses an object that already carries a charge and brings it close to the neutral metallic glass powder. Due to electrostatic induction, one side of the powder will carry the opposite charge, while the other side will carry the same charge. The ionization method can generate a large number of positive or negative ions by exposing the metallic glass powder to conditions such as high-voltage discharge devices, ultraviolet radiation or chemical reactions, thereby increasing the number of charges on the powder. A large number of positive or negative ions can be generated using a high-voltage electrostatic generator. These devices usually use electrostatic induction and separation technology to gather charges on the metallic glass powder.

[0079] The embodiment of the present invention provides a preparation method based on a metallic glass-epoxy composite film, which uses epoxy resin and curing agent liquid as a matrix; determines the preset metallic glass powder corresponding to the epoxy resin liquid according to the mass ratio; and dopes the preset metallic glass powder into the epoxy resin and curing agent liquid in the matrix to form a metallic glass-epoxy composite film. The present invention improves the performance of the composite film power generation element by doping the metallic glass powder to increase the number of mobile charges. This process changes the charge transfer characteristics, so that more shallow traps are formed in the interface area between the metallic glass powder and the epoxy resin matrix, and less energy is released in the charge carrier process. At the same time, the preset metallic glass powder determined by the mass ratio is introduced to improve the accumulation and retention of charges, thereby improving the performance and efficiency of the power generation element.

[0080] In some embodiments, the metallic glass powder is FeNiCoZr metallic glass powder, and the oxygen content of the FeNiCoZr metallic glass powder is less than 1%.

[0081] Specifically, FeNiCoZr metallic glass exhibits macroscopic ferromagnetism due to its magnetic neighbor exchange interaction, and its structural isotropy gives it small anisotropy, which makes it have excellent soft magnetic properties, including high saturation magnetic induction, low coercive force, high magnetic permeability and low loss. FeNiCoZr metallic glass has a unique topological disordered structure, which gives it excellent radiation resistance and is suitable for use in extreme environments such as nuclear energy applications. FeNiCoZr metallic glass powder can provide better mechanical support and protection in composite films due to its high strength, high hardness and high wear resistance. The preparation conditions of FeNiCoZr metallic glass powder are relatively loose and the cost is low, which makes it more cost-effective in industrial applications. FeNiCoZr metallic glass can significantly improve the fatigue resistance of the alloy, which is crucial to improving the durability and reliability of the composite film.

[0082] Low oxygen content is beneficial to improving the glass-forming ability of Fe-based alloys. This means that in FeNiCoZr metallic glass powder, lower oxygen content helps to form more amorphous structures, thereby improving the overall performance of the material. The control of oxygen content has little effect on the magnetic properties and thermal stability of Fe-based amorphous alloys, but an appropriate amount of oxygen can increase the glass-forming ability of Fe-CBP-Mo alloys. Therefore, low oxygen content in FeNiCoZr metallic glass powder helps to maintain the magnetic properties and thermal stability of the alloy. An oxygen content of less than 1% in FeNiCoZr metallic glass powder can reduce the precipitation of crystalline phases, maintain the amorphous characteristics of the alloy, and thus improve its wear resistance.

[0083] The metallic glass powder provided in this embodiment is FeNiCoZr metallic glass powder, and the oxygen content of FeNiCoZr metallic glass powder is less than 1%, which can improve the glass forming ability, improve the magnetic properties and thermal stability, reduce the precipitation of the crystalline phase, and improve the wear resistance in the preparation of the composite film.

[0084] In some embodiments, the metallic glass powder has a powder particle size of 20-50 μm.

[0085] Specifically, metallic glass powder with a particle size of 20-50µm can be used as a reinforcing phase to improve the wear resistance of the composite film, so that it can maintain the magnetic properties and thermal stability of the film when subjected to external friction. It is beneficial to optimize the aspect ratio of the particles, thereby increasing the service life of the composite film during triboelectric generation. At the same time, it provides better molding control, such as the dimensional accuracy and repeatability of the composite film. With the increase of metallic glass powder, the charge accumulation of the composite film triboelectric element changes significantly.

[0086] The metallic glass powder with a particle size of 20-50 μm provided in this embodiment improves wear resistance, thermal properties, dimensional accuracy and repeatability, surface properties and processing performance in the preparation of composite films.

[0087] Furthermore, the present invention also provides a friction power generation element, including a copper electrode layer, a charge transfer layer and a flexible friction layer; the size of the friction power generation element is 46×90mm 2 , thickness 1µm; wherein the film inside the charge transport layer is a metallic glass-epoxy resin composite film prepared according to the steps of the above-mentioned method for preparing a metallic glass-epoxy resin composite film;

[0088] The flexible friction layer is located on the outer layer of the friction power generation element and is used to generate friction charges in contact with the outside world;

[0089] The charge transfer layer is located between the flexible friction layer and the copper electrode layer and is used for transferring the friction charges to the copper electrode layer;

[0090] The copper electrode layer is located in the inner layer of the triboelectric element and is used to collect triboelectric charges.

[0091] Specifically, when there is no external force, the two electrodes of the friction power generation element are in an equipotential state and there is no potential difference. When an external force (such as sliding, pressure, vibration, etc.) acts on friction power generation, two different friction materials rub against each other, resulting in charge separation. The charges generated by friction generate an electric field near the electrode, causing the charges in the other electrode to move, thereby forming a potential difference between the two electrodes. When an external circuit is connected to the two electrodes of the friction generator, due to the existence of the potential difference, the charges will flow in the circuit to form a current. As the external force changes, the contact state and charge distribution between the friction materials will also change, resulting in a continuous change in the potential difference between the electrodes and continuous current output. Metallic glass powder doping increases the number of mobile charges, thereby improving the performance of the composite thin film power generation element. The structure of the friction power generation element includes a copper electrode layer, a metallic glass-epoxy resin composite film transmission layer, and a flexible friction layer.

[0092] For an introduction to a friction power generation element provided by the present invention, please refer to the above method embodiment, and the present invention will not be repeated here. It has the same beneficial effects as the above preparation method based on metallic glass-epoxy resin composite film.

[0093] Furthermore, the present invention also provides a wearable electronic device, comprising the above-mentioned friction power generation element.

[0094] Specifically, the friction power generation element is also called a friction nanogenerator, which can be used to provide energy for wearable devices such as smart watches, health monitoring devices, etc.

[0095] For an introduction to a wearable electronic device provided by the present invention, please refer to the above method embodiment, and the present invention will not be repeated here. It has the same beneficial effects as the above-mentioned friction power generation element.

[0096] The above is a detailed introduction to the preparation method of a metallic glass-epoxy resin composite film and a friction power generation element provided by the present invention. The various embodiments in the specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same and similar parts between the embodiments can be referenced to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the present invention.

[0097] It should also be noted that, in this specification, relational terms such as first and second, etc. are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.

Claims

1. A method for preparing a metallic glass-epoxy resin composite film, characterized in that: include: It is based on epoxy resin and curing agent liquid; Determine the preset metallic glass powder corresponding to the epoxy resin liquid according to the mass ratio; Preset metallic glass powder is doped into the epoxy resin and curing agent liquid in the matrix to form the metallic glass-epoxy resin composite film.

2. The method for preparing a metallic glass-epoxy resin composite film according to claim 1, characterized in that: The method comprises: doping a preset metallic glass powder into the epoxy resin and the curing agent liquid in the matrix, comprising: Based on room temperature, the preset metallic glass powder is rotated and mixed into the epoxy resin and the curing agent liquid in the matrix at a preset speed.

3. The method for preparing a metallic glass-epoxy resin composite film according to claim 1, characterized in that: The process of determining the mass ratio comprises: Obtaining each preset mass ratio and the mass of the epoxy resin liquid; Determining each initial preset metallic glass powder corresponding to each preset mass ratio according to each preset mass ratio and the mass of the epoxy resin liquid; According to the epoxy resin liquid corresponding to each of the preset mass ratios and the corresponding initially preset metallic glass powder, a corresponding charge quantity and a corresponding current average value are prepared; A final mass ratio is determined based on the charge quantity and / or the current average value.

4. The method for preparing the metallic glass-epoxy resin composite film according to claim 3, characterized in that: The final mass ratio is determined according to the current average value, including: Screening out the maximum current average value among the current average values ​​corresponding to the preset mass ratios; The preset mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

5. The method for preparing the metallic glass-epoxy resin composite film according to claim 3, characterized in that: Determining a final mass ratio according to the charge quantity and the current average value includes: Get the preset charge quantity; Selecting a mass ratio greater than the preset charge quantity from each charge quantity as the initial mass ratio; Screening out the largest current average value from the current average values ​​corresponding to the initial mass ratios; The initial mass ratio corresponding to the maximum current average value is taken as the final mass ratio.

6. The method for preparing the metallic glass-epoxy resin composite film according to claim 4, characterized in that: The mass ratio of the preset metallic glass powder to the epoxy resin liquid is less than 10%.

7. The method for preparing a metallic glass-epoxy resin composite film according to claim 1, characterized in that: The metallic glass powder is FeNiCoZr metallic glass powder, and the oxygen content of the FeNiCoZr metallic glass powder is less than 1%.

8. The method for preparing a metallic glass-epoxy resin composite film according to claim 1, characterized in that: The particle size of the metallic glass powder is 20-50 μm.

9. A friction power generation element, characterized in that: It includes a copper electrode layer, a charge transfer layer and a flexible friction layer; the size of the friction power generation element is 46×90mm 2 , thickness 1µm; wherein the film inside the charge transport layer is a metallic glass-epoxy resin composite film prepared by the steps of the preparation method of a metallic glass-epoxy resin composite film according to any one of claims 1 to 8 above; The flexible friction layer is located on the outer layer of the friction power generation element and is used for contacting with the outside world to generate friction charges; The charge transfer layer is located between the flexible friction layer and the copper electrode layer, and is used to transfer the friction charges to the copper electrode layer; The copper electrode layer is located in the inner layer of the friction power generation element and is used to collect the friction charges.

10. A wearable electronic device, characterized in that: It includes the friction power generation element as described in claim 9 above.

Citation Information

Patent Citations

  • Conductive thickener, electronic device and solar battery comprising electrodes formed by conductive thickener

    CN102376379A

  • Powder made of iron-based metallic glass

    CN104136147A

  • High-strength high-electric-conductivity metal-glass composite material and preparation method thereof

    CN110699676A

  • Self-driven sensor

    CN110995052A

  • Metal glass fiber / epoxy resin composite material and preparation method thereof

    CN112063107A